Remembering the Seven-Word of The Jakarta Charter: The Challenging Risk of Indonesian Today - Ahmad Salehudin (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2018)
This article aims to discuss the remembering phenomenon of the seven words of the Jakarta Charter. Even though it happened in early Indonesia independent era, the rejection of deleting the seven words of Jakarta Charter still exists until now. The seven words abolition of the Jakarta Charter became myths and rites that used by Islamic fundamentalist groups to bring back past memories in Indonesia today. In the process, it became a collective or social memory among Muslim Fundamentalist group, and it gives great energy, and also dreaming, to the fundamentalist Islamic groups to struggle to remake Indonesia as Islamic State. In Indonesian history, it is a big problem because of two reasons. Indonesia is not Islamic state. Beside that this group also is not only using constitutional ways, but also unconstitutional ways, such rebellion, religious terror, and hijacking. Therefore we need to reshape and reconfigure the memory of deleting the seven words of the Jakarta Charter.